2019
DOI: 10.3390/nu11071626
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anserine/Carnosine Supplementation on Mild Cognitive Impairment with APOE4

Abstract: Background: Oral supplementation of anserine/carnosine helps preserve cognitive functions in healthy older adults. Mild cognitive impairment (MCI) is a transition between cognitive-normal and dementia. Therefore, it needs to investigate whether anserine/carnosine supplementation (ACS) has effects on subjects with MCI. Methods: A randomized, double-blind, placebo-controlled 12-week trial was performed. Fifty-four subjects with MCI were randomized to an active group ingesting 750 mg of anserine and 250 mg of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 48 publications
0
73
0
Order By: Relevance
“…For example, oral administration of anserine (10 or 100 mg/45 kg BW in 20 ml of tap water) reduced blood glucose levels during an oral glucose tolerance test in humans . Similarly, supplementing anserine plus carnosine (1 g/day, 3:1 ratio, 3 months) to healthy elderly subjects has been shown to preserve verbal episodic memory and brain perfusion (including blood flow in the prefrontal brain (Ding et al 2018;Hisatsune et al 2015;Rokicki et al 2015), attenuate cognitive impairment (Hisatsune et al 2016;Masuoka et al 2019), inhibit the production of inflammatory cytokines by peripheral blood mononuclear cells (Katakura et al 2017), and enhance muscular strength and exercise endurance (Hirohiko et al 2006). Because avian muscle contains a large amount of anserine as noted previously, much evidence shows that consumption of a popular Asian food known as chicken essence (chicken meat extract) by humans, particularly elderly subjects, has long been a nutritional means to improve human health and prevent chronic diseases.…”
Section: Health Benefits Of Anserine Supplementationmentioning
confidence: 99%
“…For example, oral administration of anserine (10 or 100 mg/45 kg BW in 20 ml of tap water) reduced blood glucose levels during an oral glucose tolerance test in humans . Similarly, supplementing anserine plus carnosine (1 g/day, 3:1 ratio, 3 months) to healthy elderly subjects has been shown to preserve verbal episodic memory and brain perfusion (including blood flow in the prefrontal brain (Ding et al 2018;Hisatsune et al 2015;Rokicki et al 2015), attenuate cognitive impairment (Hisatsune et al 2016;Masuoka et al 2019), inhibit the production of inflammatory cytokines by peripheral blood mononuclear cells (Katakura et al 2017), and enhance muscular strength and exercise endurance (Hirohiko et al 2006). Because avian muscle contains a large amount of anserine as noted previously, much evidence shows that consumption of a popular Asian food known as chicken essence (chicken meat extract) by humans, particularly elderly subjects, has long been a nutritional means to improve human health and prevent chronic diseases.…”
Section: Health Benefits Of Anserine Supplementationmentioning
confidence: 99%
“…Remarkably, such an activation effect on CAs allows for a better understanding of many reported carnosine biological activities. As an example, several studies reported significant beneficial effects of carnosine and its analogues on cognitive impairment [29,30] and the proposed mechanisms were substantially focused on antioxidant and metal-chelation properties of these peptides which elicit anti-inflammatory and anti-aggregant neuroprotective effects. [31] Since the CA activators are emerging for their capacity to enhance cognition and memory [10,11], the here reported results suggest that the beneficial effects of histidine containing dipeptides on brain activity can be also ascribed to their activating effects on CA isozymes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to sports application, the discovery of the underlying mechanism may ultimately also lead the way to more therapeutic applications. Interestingly, the bene cial effects of the ingestion of carnosine and anserine mixtures are currently investigated and demonstrated for a number of applications, such as for cognitive function in elderly [33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%